Physical environment and blood glucose level of diabetic patients: A cross-sectional study - Yesi Hasneli; Dedi Afandi; Elda Nazriati; Nofrizal (Journal of the Pakistan Medical Association)
Objective: To determine the correlation between physical environment and blood glucose levels in diabetic patients. Method: The quantitative, cross-sectional study was conducted from July to October 2022 at the Rejosari Pekanbaru Community Health Centre, Indonesia, and comprised diabetic patients of either gender with a disease history of at least 3 years. Environmental temperature was considered acceptable at 18-20°C, while environmental light was considered acceptable at 60-120 lux. Random blood glucose level <60mg/dL was taken as low, 70-130 mg/dL normal, and >140 mg/dL high. The correlation between physical environment and blood glucose level was worked out. Data was analysed using SPSS 20. Results: Of the 125 subjects, 89(71.2%) were females and 36(28.8%) were males. There were 45 patients aged 56-65 years and 11(8.8%) were aged <11 years. Overall, 90(72%) patients had high random blood sugar and 35(28%) had normal level. The disease duration was <5 years in 79(63.2%) cases and >5 years in 46(36.8%). Of the 80(64%) patients who lived in an unacceptable living room temperature, 63(78.8%) had high random blood glucose levels (p=00042). Of the 73(58.4%) patients who lived in an unacceptable living room light, 59(80.8%) had high random blood glucose (p=0.016). Conclusion: A significant effect of temperature and light was found on blood glucose levels in diabetic patients. Keywords: Diabetes, Temperature, Light, Glucose.